Design a mobile application for vehicles managing of a transportation issue - Seddiq Q. Abd Al-Rahman; Sameeh Abdulghafour Jassim; Ali Makki Sagheer (Bulletin of Electrical Engineering and Informatics, 2021)
The movement of people between cities is leading to a recovery in the economy that transportation companies have begun to dominate. These companies start providing the best services to customers and promoting them through workers to earn money properly. From this basis, this paper presents a system designed to manage a company that transports people and goods between a group of cities. Database management was used across the web to enable data exchange between workers. The database is designed to be accessible to workers. It has also been suggested that the elliptic curve can be used to generate public and private keys for all parties while the company's management generates a prime number every day to ensure the confidentiality of the exchanged data. In this proposal, the rivest-shamir-adleman (RSA) algorithm is used to encrypt transferred data. It uses technology to exchange information if the recipient is not connected to the network. The proposed system performs a good service for the company’s management in securing the transferred data where smartphone applications are designed to work on it.